PROCESSING AND EVALUATION OF TONIC HAIR EXTRACT OF SINGKONG LEAVES (Manihot esculenta Crantz): COMBINATION OF ROSE WATER SQUEEZED (Rossa sp) IN MALE RABBITS - Sofia Rahmi Tambusai; Dian Ika Pebrina Meliala; Desi Damayanti (JBIO: jurnal biosains (the journal of biosciences), 2022)
Hair growth cosmetics that make hair grow and stimulate hair growth due to baldness and hair loss are often called hair tonics. The alternative to natural ingredients used for hair tonic cosmetics as hair growth by rubbing then on the scalp, cassava leaves are used which can accelerate hair growth and reduce the occurrence of hair loss because the cassava leaves contain vitamin C and organic compounds, such as flavonoids, tannins, triterpenoids, and saponins. Hair tonic processing in this study used an experimental method by processing cassava leaves into extracts with a concentration of 5%; 7.5% and 10%, mixed with additional ingredients in the form of rose water juice, propylenglycol, nipagin, nipasol, BHT, menthol, and methyl paraben. These preparations were then tested on male rabbits weighing 1.5-2 kg, and Observed for four weeks. Processed hair tonic is given in an orderly manner in the specified part. Extracting hair used tweezers so that it can be observed. In the 20 plucked hairs, choosen the 10 longest strands of hair and measure them with a caliper. The period of hair removal is once a week. This research concluded that the processed hair tonic of cassava leaf extract, a combination of rose water juice, can be processed at a concentration of 5%; 7.5%, and 10%. The 10% concentration of hair tonic in the cassava leaf extract, the combination of the juice of rose water, resulted in a better hair length growth of 0.30 mm when compared to Natur's processing of 0.25 mm.